Inhibiting the phosphoinositide 3-kinase pathway for cancer treatment. (1st April 2004) - Workman, P.
Abstract : There is extensive evidence from the molecular and genomic analysis of human cancers that the PI 3-kinase (phosphoinositide 3-kinase)–Akt/PKB (protein kinase B) pathway is deregulated in malignant progression. Furthermore, the causal involvement of PI 3-kinase is supported by gene-knockout mouse models. Prototype inhibitors show evidence of anticancer activity in vitro and in vivo animal models. The recent development of isoform-selective inhibitors shows considerable promise for cancer treatment.